Nilai-Nilai Pendidikan Islam dalam Novel ‘Merindu Baginda Nabi’ Karya Habiburrahman El Shirazy - Suryati, Dini; Arifah, Chusna; Fitri, Sofia Ratna Awaliyah (Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID), Ciamis, Jawa Barat, Indonesia, 2020)
This study aims to determine the values ​​of faith education, the values ​​of religious education, and the values ​​of moral education. The method used in this data analysis is the documentation method, the documentation method as an effort to obtain data and information in the form of written notes or images that are stored related to the problem under study. In this study the authors examined books and other sources related to the object of research, such as articles, the internet, and other books relating to the values ​​of Islamic education in the novel Merindu Baginda Nabi. In the novel Merindu Baginda Nabi, written by Habiburrahman El Shirazy, it can be concluded that: 1) The values ​​of faith education in the novel